2023
DOI: 10.1002/anie.202311241
|View full text |Cite
|
Sign up to set email alerts
|

Selective Gas‐Phase Hydrogenation of CO2 to Methanol Catalysed by Metal‐Organic Frameworks

Amarajothi Dhakshinamoorthy,
Sergio Navalón,
Ana Primo
et al.

Abstract: Large scale production of green methanol obtained from CO2 and green hydrogen is a highly wanted process due to the role of methanol as hydrogen/energy carrier and for the production of chemicals. Starting with a short summary of the advantages of metal‐organic frameworks (MOFs) as catalysts in liquid‐phase reactions, the present article highlights the opportunities that MOFs may offer also for some gas‐phase reactions, in particular for the selective CO2 hydrogenation to methanol. It is commented that there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 111 publications
(194 reference statements)
0
4
0
Order By: Relevance
“…The hydrogel microspheres were formed immediately and immersed in NaOH solution for 2 h and then profusely washed with distilled water to pH 7. Afterwards, the resulting hydrogel microspheres were washed by a series of ethanol/water baths with an increasing concentration of ethanol (10,30,50,70,90, 100 vol.%, respectively) for 15 min in each and immersed in 100 mL Cu(OAc) 2 -ethanol solution with different concentrations, as indicated in Table S1, for 2 days with a slow stirring, then washed with anhydrous ethanol, and subsequently dried by supercritical CO 2 . Drying using supercritical CO 2 ensures high porosity and large surface area of the aerogel microspheres in comparison with alternative drying procedures [44].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogel microspheres were formed immediately and immersed in NaOH solution for 2 h and then profusely washed with distilled water to pH 7. Afterwards, the resulting hydrogel microspheres were washed by a series of ethanol/water baths with an increasing concentration of ethanol (10,30,50,70,90, 100 vol.%, respectively) for 15 min in each and immersed in 100 mL Cu(OAc) 2 -ethanol solution with different concentrations, as indicated in Table S1, for 2 days with a slow stirring, then washed with anhydrous ethanol, and subsequently dried by supercritical CO 2 . Drying using supercritical CO 2 ensures high porosity and large surface area of the aerogel microspheres in comparison with alternative drying procedures [44].…”
Section: Methodsmentioning
confidence: 99%
“…Being in the liquid state at ambient conditions, methanol has other important advantages compared to alternative products formed in CO 2 hydrogenation, including water solubility, non-corrosiveness, high volumetric energy content, and easy transformation into gasoline [ 4 , 5 ] and aromatics [ 6 , 7 ], among other chemicals [ 8 , 9 ]. Although methanol is currently produced on a large multi-ton scale, and there was an estimated 100 millions of metric tons produced in 2020, there is still the possibility to considerably increase methanol production [ 10 ], particularly if application of methanol as a fuel or hydrogen carrier is finally implemented [ 11 , 12 , 13 ]. In any case, market forecasts indicate that methanol production will at least double by 2030 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present level of burning fossil fuels to meet the world’s energy requirements is steadily raising the CO 2 emissions released into the atmosphere and is responsible for global warming and climate change. , There is thus an urgent need to shift from these fuels to renewable energy obtained from natural resources like the sun, wind, water, or biomass. , The development of technologies based on carbon-free energy carriers like green hydrogen is considered vital to help decarbonize the world’s economies, , whereas carbon capture, storage, and utilization (CCSU) are some processes that can minimize the negative effects of CO 2 emissions. , Even though certain CCS processes have achieved relative success, most of the technologies used to convert CO 2 into valuable products or fuels are still under development, including solar-assisted photocatalysis, which is considered to be a promising cost-efficient and sustainable process for recycling CO 2 . In 1978, a pioneering study reported on the possibility of reducing CO 2 using GaP as the photoelectrocatalyst . Since then, many other inorganic semiconductors , and, more recently, perovskites, , carbon-based materials similar to graphenes, ,, or carbon nitrides, , among others, , have been used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Due to the pore confinement effect, metal NPs are embedded in the MOFs pore with controllable sizes, [36] which leads to improved activity and selectivity in oxidation and hydrogenation applications. [38][39][40] One of the MOF types that received significant attention as a catalytic material is Zirconium-based MOFs such as UiO-66 due to their good chemical and mechanical stability. [9,41] It has been successfully used as a catalytic material for a variety of reactions such as Suzuki coupling, [42,43] carbon dioxide hydrogenation, [44] methanation, [45] prisn reaction, [46] dehydrogenation, [47] and ethanol upgrading reaction.…”
Section: Introductionmentioning
confidence: 99%